PENGARUH LEVERAGE, PROFITABILITAS, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Yanah, Fitri Serli; Sufiyati, Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research was conducted with the aim of determining the effect of leverage, profitability, liquidity, and company size on company value in primary consumer sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Purposive sampling method is used in conducting sample selection. A total of 52 companies were used in this study. This study uses technique multiple regression analysis and assisted by the SPSS program in performing data processing. The results of this study show that profitability has a significant effect on the value of the company, while leverage, liquidity, and company size do not have a significant influence on the value of the company. The implications in this study are expected that the company can increase profit in order to increase the value of the company so that it can provide positive signals for investors.